Integrated Special Education Program Students Involvement of the Woodworking Training Skills by Using Teaching Aid - A. Shah, Aziezatul Nezirah Amri, Mohamed nor Azhari Azman; Kassymova, Gulzhaina K. (Opción, 1970)
This research aims to develop a Teaching Aid which is Smart Cot to be included in the Furniture Manufacturing Basics subject introduced by the Ministry of Education specifically for special needs students for the Integrated Special Education Program based on learning problems. The method used in this research is the qualitative method through interview, observation, and checklist form. Researchers recommend that the teaching aid Smart Cot can be used by teachers in the teaching and facilitation process on the topic of Furniture Making Basics to special needs students in order to improve their performance and mastery of woodworking skills.